Study of microbiological aspects of meningoencephalitis due to Listeria spp in ruminants - GIANNATI-STEFANOU (Α. ΓΙΑΝΝΑΤΗ-ΣΤΕΦΑΝΟΥ) A.; TSAKOS (Π. ΤΣΑΚΟΣ) P.; BOURTZI-HATZOPOULOU (Ε. ΜΠΟΥΡΤΖΗ-ΧΑΤΖΟΠΟΥΛΟΥ) E.; ANATOLIOTIS (Κ. ΑΝΑΤΟΛΙΩΤΗΣ) K. (Journal of the Hellenic Veterinary Medical Society, 2017)
Microbiological aspects of meningoencephalitis due to Listeria spp in Northern Greece were studied. The diagnosis was based on the isolation of Listeria monocytogenes from bovine, sheep and goats brains. Forty three bovine herds, 310 sheep flocks and 976 goat herds, suspicious of the neural form of listeriosis, were examined and 2 (4.6%), 60 (19.3%) and 361 (36.9%) of them were found positive, respectively. It was ascertained statistically (P<0.05) that encephalitic listeriosis affects mostly goats than sheep. All strains, except two, were isolated from adult animals mostly in December and January. Sero typing of 141 strains showed that serovar 4b was predominant (81%) and was distributed among all the areas where listeriosis was detected. Phage typing of 60 strains allowed the clustering of strains, those belonging to the same serotype and phage lysed by the same phage or a series of phages. These groups were found mainly in bordering areas with few exceptions. This fact probably shows the common origin of these strains.